Learning Physics with a Free Discovery Model to Improve Critical Thinking Skills of High School Students - Zahrotul Wafa; Budi Jatmiko (IKIP Mataram, 2022)
Critical thinking abilities are extremely important in 21st-century learning. The goal of this study was to determine the effectiveness of the free discovery learning paradigm in developing high school students' critical thinking skills. The research approach was a one-group pre-test and post-test design with repeated pre-experimental research without a control group. Before learning, students were given a pre-test, and after learning, they were given a post-test with the same material. The sample used in the study comprised 72 MAN Sidoarjo students divided into two classes, namely class XI MIPA 6 and XI MIPA 7. Critical thinking skills tests and student response questionnaires were utilized as instruments in this study. Paired t-tests, n-gain calculations, independent t-tests, and student response questionnaire analyses were among the data analysis approaches used in this study. With an average n-gain score included in the moderate criteria in the two experimental classrooms, the value of students' critical thinking skills increased.There was no difference in the average n-gain value between the two experimental classes. The average percentage of student responses to learning the free discovery model was in the excellent category of 81.56% and 80.78%. So, it can be concluded that the free discovery learning model effectively improves the critical thinking skills of high school students. This study implies that physics learning with a free discovery model can be helpful for teachers in improving the critical thinking skills of high school students.